The Relationship between Effective Communication of Nurses and the Level of Patient Satisfaction in the Inpatient Installation of Mandau Duri Regional Hospital in 2019 - Rina Yulviana; Yessi Harnani; Widia Oktaviani (Institute Of Computer Science (IOCS), 2020)
The nursing process is never out of the process interactions that occur between nurses and patients that nurses should be aware that to communicate effectively in professional nursing practice very influential or assist the patient in the healing process or in fulfilling their basic needs during hospitalization. Service quality issues in hospitals Saber Duri still far from what is expected of society, one patient told nurses seem unfriendly, do not care about the complaints and diseases of the patient, and also like to delay in providing nursing care. This study aims to determine the relationship of effective communication nurse with patient satisfaction level at inpatient hospitals Saber Duri Year 2019 type of quantitative research with cross sectional design allnurses inpatient amounted to 108 people with a sample of 85 respondents. The sampling technique stratified random sampling. Data analysis was performed using univariate and bivariate with chi-square test (? = 0.05). The results of the bivariate analysis of six variables there are five of them found a significant relationship between attitude (? = 0.046?? = 0.05), communication (? = 0.011 ?? = 0.05), perception (? = 0.001 ?? = 0.05), facilities (? = 0.004 ?? = 0.05), and environmental (? = 0.025 ?? = 0.05), while the variable no significant relationship between gender (? = 0.239 ?? = 0.05) with patient satisfaction. Then the conclusions and suggestions for hospitals Saber Duri to improve human resources such as nurses, and maintain his skill in communicating effectively with patients, as well as complementary facilities inpatient room.